Ensuring Food Integrity by Metrology and FAIR Data Principles - Rychlik, Michael; Zappa, Giovanna; Añorga, Larraitz; Belc, Nastasia; Castanheira, Isabel; Donard, Olivier F. X.; Kouřimská, Lenka; Ogrinc, Nives; Ocké, Marga C.; Presser, Karl; Zoani, Claudia (Frontiers in Chemistry, 2018)
Food integrity is a general term for sound, nutritive, healthy, tasty, safe, authentic, traceable, as well as ethically, safely, environment-friendly and sustainably produced foods. In order to verify these properties, analytical methods with a higher degree of accuracy, sensitivity, standardization and harmonization and a harmonized system for their application in analytical laboratories are required. In this view, metrology offers the opportunity to achieve these goals. In this perspective article the current global challenges in food analysis and the principles of metrology to fill these gaps are presented. Therefore, the pan-European project METROFOOD-RI within the framework of the European Strategy Forum on Research Infrastructures (ESFRI) was developed to establish a strategy to allow reliable and comparable analytical measurements in foods along the whole process line starting from primary producers until consumers and to make all data findable, accessible, interoperable, and re-usable according to the FAIR data principles. The initiative currently consists of 48 partners from 18 European Countries and concluded its “Early Phase” as research infrastructure by organizing its future structure and presenting a proof of concept by preparing, distributing and comprehensively analyzing three candidate Reference Materials (rice grain, rice flour and oyster tissue) and establishing a system how to compile, process and store the generated data and how to exchange, compare them and make them accessible in data bases.